Film and the same manufacturing method
The film, composed of multiple layers of polyester resin with a high percentage of recycled content, effectively maintains color and mechanical properties, addressing the limitations of existing recycling methods and reducing environmental impact.
Patent Information
- Application Number
- JP2023149798
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-15
- Publication Date
- 2025-03-28
AI Technical Summary
Existing methods for recycling polyester films often result in a decline in mechanical strength and color characteristics, limiting the amount of recycled polyester resin that can be used without increasing the color tone b value of the film.
A film composed of 100 to 1,000 layers of polyester resin, with 30% to 100% recycled polyester resin by mass, where the average thickness of each layer is 10 nm to 1,000 nm, and the tone b value is maintained between -2.0 and 2.0, thereby suppressing the increase in color tone b value.
The proposed solution allows for the use of a high percentage of recycled polyester resin without increasing the color tone b value of the film, maintaining transparency and mechanical strength, and reducing environmental impact.
Smart Images

Figure 2025042708000001 
Figure 2025042708000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a film containing recycled polyester resin and a method for producing the same. [Background technology]
[0002] For many years, efforts have been made to reuse polyester scraps generated during the manufacture of polyester resin molded products. As a method for recycling such polyester scraps, material recycling has been carried out in which the polyester scraps are once melted and pelletized, and then used as recycled polyester resin material. However, since the recycled polyester resin obtained in this way is prone to some degradation in quality, it has been blended in a certain amount with other virgin polyester resins and used within a limited range where the quality of the polyester resin molded products is not degraded.
[0003] Furthermore, due to the recent increase in environmental awareness, such as the SDGs, the target of recycled polyester resin moldings is expanding to include used polyester scraps that were once distributed to the market or consumers. Used polyester scraps that were distributed in the market are collected, and the functional layer provided on the surface of the collected polyester resin molding is peeled off and removed. Depending on the peeling method, solvents for peeling and foreign matter are washed away, and only the polyester film is extracted and processed again as polyester resin. In particular, polyester films used as substrates in the manufacturing process of polarizing plates and ceramic green sheets tend to be discarded without being reused after the target object is peeled off from the substrate, due to the dimensional change of the substrate caused by processing. Even if it is recycled into other products as recycled polyester resin, films using recycled polyester resin tend to have deteriorated properties such as mechanical strength and color compared to films using virgin resin, and there is a limit to the amount of recycled polyester resin that can be used. In response to this problem, for example, Patent Document 1 proposes a method of pretreating the film before recovery by providing a layer containing an antioxidant, which prevents the deterioration of the coating layer components during melting and prevents the coloring of the recycled film, since when the recovered film is melted and recycled, the adhesive coating and antistatic coating attached to the film surface deteriorate and cause the recycled film to become discolored. Also, for example, Patent Document 2 proposes a technology of adding a recycled resin to an intermediate layer and an ultraviolet absorber to the outer layer to suppress the deterioration of the recycled resin due to ultraviolet light and yellowing. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Japanese Patent Application Publication No. 08-217892 [Patent Document 2] JP2012-210761 Public Relations Summary of the Invention [Problem to be solved by the invention]
[0005] However, in the method of Patent Document 1, in order to regenerate polyester resin, a layer containing another ultraviolet absorber is laminated on the surface of the film, which uses another resource, and this puts a burden on the environment. In addition, since recycled polyester resin containing ultraviolet absorber is used, the amount of ultraviolet absorber added increases as the amount of recycled polyester resin used increases, which makes transparency more likely to be impaired. In addition, in the method of Patent Document 2, adding an ultraviolet absorber to the outer layer reduces the film formability, so recycled polyester resin cannot be used in the outer layer, and the amount of recycled polyester resin used in the middle layer is limited from the viewpoint of film transparency and color issues.
[0006] An object of the present invention is to provide a film in which the increase in the color tone b value of the film is small even when a large amount of recycled polyester resin is added as desired. [Means for solving the problem]
[0007] In order to solve the above problems, a preferred embodiment of the present invention has the following configuration. (1) A film having 100 to 1,000 polyester resin layers laminated together, the film containing 30% to 100% by mass of recycled polyester resin relative to the total mass of the polyester resin constituting the film. (2) The film according to (1), wherein the average thickness of the polyester resin layer is 10 nm or more and 1,000 nm or less. (3) The film according to (1) or (2), wherein the color tone b value of the film is −2.0 to 2.0. (4) The film according to any one of (1) to (3), wherein the color tone b value of the polyester resin constituting the film is more than 4.0 times the color tone b value of the film. (5) The film according to any one of (1) to (4), wherein the color tone b value of the polyester resin is 5.0 or more and 15.0 or less. (6) The film according to any one of (1) to (5), wherein the color tone b value of the recycled polyester resin is 5.0 or more and 30.0 or less. (7) The polyester film according to any one of (1) to (6), wherein the haze value of the film is 2.0% or less. (8) The film according to any one of (1) to (7), wherein the thickness T (μm) of the film is 25 μm or more and 500 μm or less. (9) A method for producing a film comprising 100 to 1,000 polyester resin layers according to any one of (1) to (8), wherein the film contains 30% by mass or more and 100% by mass or less of recycled polyester resin based on the total mass of the polyester resin constituting the film. Effect of the Invention
[0008] According to the present invention, it is possible to provide a film in which the increase in the color tone b value of the film is small even when a large amount of recycled polyester resin is added as desired. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] The film of the present invention is a film formed by laminating polyester resin layers in a number ranging from 100 to 1000. The polyester resin layers refer to layers containing polyester resin as a main component. The polyester resin is a polyester obtained by using an aromatic dicarboxylic acid or an aliphatic dicarboxylic acid and a diol or a derivative thereof. Here, examples of aromatic dicarboxylic acids include terephthalic acid, isophthalic acid, phthalic acid, 1,4-naphthalenedicarboxylic acid, 1,5-naphthalenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, 4,4'-diphenyldicarboxylic acid, 4,4'-diphenyletherdicarboxylic acid, and 4,4'-diphenylsulfonedicarboxylic acid. Examples of aliphatic dicarboxylic acids include adipic acid, suberic acid, sebacic acid, dimer acid, dodecanedioic acid, cyclohexanedicarboxylic acid, and ester derivatives thereof. Among these, terephthalic acid and 2,6-naphthalenedicarboxylic acid are preferable. These acid components may be used alone or in combination of two or more, and may be partially copolymerized with oxyacids such as hydroxybenzoic acid. Examples of the diol component include ethylene glycol, 1,2-propanediol, 1,3-propanediol, neopentyl glycol, 1,3-butanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,2-cyclohexanedimethanol, 1,3-cyclohexanedimethanol, 1,4-cyclohexanedimethanol, diethylene glycol, triethylene glycol, polyalkylene glycol, 2,2-bis(4-hydroxyethoxyphenyl)propane, isosorbate, and spiroglycol. Among these, ethylene glycol is preferably used. These diol components may be used alone or in combination of two or more. Among the above polyesters, it is preferable to use a polyester selected from polyethylene terephthalate and its copolymers, polyethylene naphthalate and its copolymers, polybutylene terephthalate and its copolymers, polybutylene naphthalate and its copolymers, and further polyhexamethylene terephthalate and its copolymers, and polyhexamethylene naphthalate and its copolymers.
[0010] A preferred embodiment of the film of the present invention is a film formed by laminating 100 to 1000 polyester resin layers. In the manufacturing process, the film of the present invention is a film in which polyester resin is supplied in a molten state to an extruder, and extruded into a sheet shape by a T-shaped die or the like as a molten laminate through a plurality of laminated paths of a lamination device, and each layer constituting the film corresponds to the plurality of paths. The number of layers of the film of the present invention is preferably 150 or more, further 200 or more, and more preferably 500 or more, from the viewpoint of suppressing an increase in the color tone b value of the polyester film. The upper limit of the number of layers is 1000 or less from the viewpoint of suppressing layer disorder in which the layer thickness is non-uniform, and from the same viewpoint, it is more preferably 700 or less.
[0011] As a method for forming a large number of layers in a film, for example, a polyester resin layer (conveniently referred to as layer A) and a polyester resin layer (conveniently referred to as layer B) are alternately laminated, and the layers A and B are alternately laminated with their surfaces directly in contact with each other. Increasing the composition types of the layers to be laminated will increase the number of extruders, so from the viewpoint of minimizing the manufacturing equipment and reducing the environmental load, for example, it is preferable to alternately laminate the above-mentioned layers A and B. In addition, the surface layers of the polyester film may have the same composition or different compositions. The composition between layers A and the composition between layers B are preferably the same composition between each layer. Furthermore, the composition of layers A and B may be the same composition, and a pseudo-lamination that becomes a single layer film when made into a film may be used. In addition, the composition of the polyester resin layers is different means that the raw material type of the polyester resin constituting each polyester resin layer or the composition ratio of the raw material type of the polyester resin is different, and the composition is the same means that the raw material type of the polyester resin constituting each polyester resin layer and the composition ratio of the raw material type of the polyester resin are both the same.
[0012] The film of the present invention contains recycled polyester resin. The recycled polyester resin refers to a polyester resin that is once melted and molded, which is mechanically recycled and remelted to pelletize, i.e., pelletized. Molded products of polyester resin include fibers, nonwoven fabrics, films, bottles, etc., but films are preferred. Films that can be collected include unused film scraps generated during the film manufacturing process and films that have been shipped outside the factory and are now used.
[0013] As a method of mechanical recycling, a film is cut into flakes and melted and solidified to produce a recycled polyester resin, or a film is melt-extruded and solidified into pellets to produce a recycled polyester resin. When producing a recycled polyester resin, if a functional layer or foreign matter is attached to the film, the film is immersed in an alkaline solvent or the like to separate the functional layer or foreign matter from the film, and the film is washed with water, and then only the film is taken out and used as a raw material for the recycled polyester resin. Examples of functional layers include a hard coat layer, a refraction adjustment layer, and an easy-adhesion layer that facilitates lamination with other members, which are typical of functional layers of optical films, and a release layer, which is typical of a release sheet, and a layer on which residues of the released material remain.
[0014] The film of the present invention can contain 30% by mass or more and 100% by mass or less of recycled polyester resin relative to the total mass of the polyester resin constituting the film, and more preferably 30% by mass or less and 80% by mass or less. The content of recycled polyester resin in each layer is not limited, but in order to maximize the amount of recycled polyester resin used as a film, it is preferable that all layers constituting the present invention contain recycled polyester resin, and the content of recycled polyester resin in each layer is preferably 30% by mass or more and 100% by mass or less, and more preferably 30% by mass or more and 80% by mass or less, relative to the total mass of the polyester resin in each layer.
[0015] The content of the recycled polyester resin in each layer may be different or the same for all layers constituting the film, and the content of the recycled polyester resin in Layer A and Layer B may be different.
[0016] In the film of the present invention, the average thickness of each polyester resin layer is preferably 10 nm or more and 1000 nm or less. The average thickness of each polyester resin layer is the average thickness per layer. In the film of the present invention, the thinner the layer thickness, the easier it is to suppress the increase in the color tone b value and haze value of the polyester film, so the average thickness of each polyester resin layer is more preferably 500 nm or less, and further preferably 350 nm or less. The thickness distribution between each layer is preferably such that the difference between the thickness of any one polyester resin layer and the average thickness of all other polyester resin layers is within 80% to 120%, preferably 90% to 115%, more preferably 95% to 105%, and ultimately the difference is 0%. In the film of the present invention, since the average thickness of each polyester resin layer is thin, even if the difference in the average thickness of the polyester resin layer between each polyester resin layer is about ±20%, it is unlikely to affect the color tone b value when made into a film. In order to increase the rigidity and flatness of the film, it is conceivable that a thick polyester resin layer may be formed on the surface side of the film. However, a surface layer having a thickness of more than 1.0 μm when made into a film is excluded from the layers defined in the present invention.
[0017] In order to make each layer have the same thickness, it is possible to appropriately adjust the lamination unevenness at the extrusion port and adjust the filtration pressure of the extruder, thereby making it easier to achieve a uniform layer thickness.
[0018] The color tone b value of the film of the present invention is preferably -2.0 to 2.0. When the color tone b value is within this range, the apparent transparency of the polyester film is not impaired, which is preferable. More preferably, the color tone b value of the polyester film is -1.0 to 1.0. Since the film of the present invention uses recycled polyester resin, the color tone b value of the film tends to increase.
[0019] Although the reason why the film of the present invention can suppress the increase in the color tone b value is not clear, it is generally believed that when the crystallization of the polyester resin is promoted and the crystal size becomes large, light with a wavelength of around 400 to 500 nm is reflected, whereas when the crystal size is small, the light transmittance in the wavelength region of around 400 to 500 nm increases. Therefore, it is believed that by limiting the region where the crystals of the polyester resin grow from the thickness of the film to the thickness of the film layer, crystallization is suppressed and the increase in the color tone b value when made into a polyester film is suppressed. Therefore, even if the thickness of each layer is larger than the wavelength, the crystal size becomes small, so the smaller the thickness of the layers constituting the film, the more the increase in the color tone b value is suppressed, and the thinner the layer thickness, the greater the effect. In addition, it is believed that the film of the present invention has 100 layers or more and 1000 layers or less, and therefore interference between the refractive indexes of each layer occurs, suppressing the increase in the color tone b value of the polyester film. Generally, interference reflection occurs at the interface of materials due to the relationship between refractive index and thickness. However, in the layer configuration of the present invention, it is considered that the color tone and refractive index of each polyester resin and the thickness of each layer reduce reflection in the wavelength region of 400 to 500 nm, i.e., the blue reflection region, thereby suppressing an increase in the color tone b value.
[0020] The film of the present invention can have a color tone b value of the polyester resin constituting the film that is more than 4.0 times the color tone b value of the film. Even if the film of the present invention contains recycled polyester raw materials, the number of layers of the film is 100 to 1000, so that the color tone b value can be easily reduced. The color tone b value of the polyester resin constituting the film is more than 4.0 times the color tone b value of the film, in other words, the color tone b value of the film is reduced to less than 1 / 4 of the color tone b value of the polyester resin. In order to maximize the use of recycled polyester resin, the color tone b value of the polyester resin constituting the film is preferably 6.0 or more, more preferably 10.0 or more, more preferably than the color tone b value of the film. In addition, when multiple types of polyester resins are contained in the polyester film, the color tone b value of each resin is a weighted average with respect to the total mass of the polyester resin composition (100% by mass). The upper limit is not particularly limited, but is influenced by the color tone b value of the recycled polyester resin constituting the polyester film and the blending with the color tone b value of other polyester resins, so it is 20.0 or less from the viewpoint of the content of recycled polyester resin.
[0021] The color tone b value of the polyester resin constituting the film of the present invention is 5.0 or more and 15.0 or less. By setting it in this range, the color tone b value of the film of the present invention can be significantly reduced. It is more preferably 6.0 or more and 14.0 or less. Since the color tone b value tends to increase as the amount of recycled polyester resin contained in the polyester resin increases, the color tone b value of the polyester resin can be set in this range by adjusting the color tone b value and the content of the recycled polyester resin.
[0022] The color tone b value of the recycled polyester resin contained in the polyester resin constituting the film of the present invention is preferably 5.0 or more and 30.0 or less. If the color tone b value of the recycled polyester resin exceeds 30.0, it is considered that the crystallization of the polyester resin has progressed, and it becomes difficult to adjust the color tone b value of the polyester film to 2.0 or less. If the color tone b value of the recycled polyester resin is more preferably 5.0 or more and 25.0 or less, and even more preferably 5.0 or more and 20.0 or less, it is easy to adjust the color tone b value of the polyester film to -2.0 or more and 2.0 or less.
[0023] Usually, when a polyester resin with a high color tone b value is used, the color tone b value of the film tends to be high as well. However, by using the configuration of the present invention, it is possible to suppress an increase in the color tone b value of the polyester film even if the polyester resin with a high color tone b value is contained.
[0024] The haze value of the film of the present invention is preferably 2.0% or less. If it is 2.0% or less, the polyester film can have high transparency. From the viewpoint of transparency, it is preferably 1.5% or less, more preferably 1.2% or less, and even more preferably 1.0% or less.
[0025] In order to suppress the increase in the haze value of the film, it is preferable that the film of the present invention does not substantially contain additives. Examples of additives include particles, ultraviolet absorbers, and antioxidants. Adding particles to a polyester film may be undesirable because it promotes the crystallization of the polyester resin and tends to increase the haze value of the polyester film. If an ultraviolet absorber or an antioxidant is added, these components tend to bleed out to the surface layer of the film when the film is heated, and the film may become white and the haze value may increase. The same applies to aging such as when the film is stored for a long period of time. According to the configuration of the present invention, the color tone b value of the polyester film can be reduced even if a large amount of recycled polyester resin is contained, so there is no need to actively add ultraviolet absorbers or antioxidants to adjust the color tone b value of the film. In the present invention, substantially no additives means that the content of additives is 0.05% by mass or less, more preferably 0.01% by mass or less, and even more preferably no additives are contained, relative to the total mass of the polyester film. It is preferable that the film of the present invention has an increase in haze value ΔHz value (%) of 1.0% or less after heating at 150° C. for 30 minutes. As described above, by not including an ultraviolet absorber or an antioxidant, it is possible to suppress an increase in haze of the polyester film after heating.
[0026] The thickness T (μm) of the film of the present invention is preferably 25 μm or more and 500 μm or less. The thickness is not particularly limited, but is preferably 300 μm or less from the viewpoint of suppressing layer disorder of the film. The thickness does not include the thickness of the easy-slip layer, adhesive layer, release layer, functional layer, etc. provided on the film surface extrusion-formed from polyester resin. If the thickness of the polyester film is less than 25 μm or exceeds 500 μm, the layer thickness may become uneven or the film may break during the manufacturing process.
[0027] In the present invention, the surface layer of the polyester film may further include a lubrication layer, an adhesive layer, a release layer, a functional layer, etc. The lubrication layer may include a water-soluble resin to which a certain amount of organic or inorganic particles are added, the adhesive layer may include a water-soluble resin to which a functional group is added, the release layer may include a silicone release functional resin or a silicone-free release functional resin, and the functional layer may include a hard-coated curable resin, a thermoplastic resin utilizing refraction, or a curable resin.
[0028] A preferred embodiment and example of the method for producing the film of the present invention will be described below.
[0029] The recycled polyester resin is not particularly limited as long as it is made of polyester as a main component. In addition, the film of the present invention can be provided by blending other polyester resins in addition to the recycled polyester resin. When a functional layer is laminated on a polyester film to be recycled, the recycled polyester resin can be provided by immersing the film in a chemical such as an alkali to dissolve and remove only the functional layer, or by scraping off the functional layer by mat processing or the like. In these methods, it is preferable to wash with water to remove the chemical, polymer powder when scraped off, and foreign matter that originally adhered when reused. Furthermore, it is preferable to crush the film from which the functional layer has been removed and dry it at a glass transition temperature to about 160 ° C. to remove moisture. It is preferable to reduce the moisture content after drying to about 100 ppm or less. The dried crushed film is melted in an extruder, extruded from a die in the form of a strand, and rapidly cooled and solidified with cold water. It is preferable to reduce the time of melting in the extruder to suppress thermal degradation. In addition, it is also a preferred embodiment that the solidified strands are cut into pellets by a strand cutter, and then the surfaces of the pellets are crystallized by a hot air dryer or the like in order to prevent fusion during the drying process during film formation.
[0030] Next, the polyester resin that constitutes each layer and that is substantially free of particles is mixed with the above-mentioned recycled polyester resin in a predetermined ratio and dried. As an example of layer formation, the polyester resin is supplied in a molten state to two extruders, extruder A corresponding to polyester resin layer A and extruder B corresponding to polyester resin layer B, and the molten thermoplastic resin from each flow path is then melt-extruded into a sheet using a known lamination device, such as a multi-manifold type feed block and a square mixer, or a lamination device having at least 100 layers and up to 1,000 layers using only a comb type feed block. The molten laminate is then melt-extruded into a sheet using a T-type die or the like, and then cooled and solidified on a casting drum to obtain an unstretched multilayer laminate film.
[0031] Methods described in JP 2007-307893 A, Japanese Patent No. 4691910, and Japanese Patent No. 4816419 can be used to improve the lamination accuracy of Layer A and Layer B. The melt extrusion conditions for the polyester resin in each extruder are preferably such that the temperature inside the extruder is at least the melting point (Tm) + 20°C, and the temperature from the extruder outlet to the slit die is at most the melting point (Tm) + 15°C.
[0032] The polymer melted and extruded in the extruder is filtered through a filter. Even the smallest foreign matter can become a large protrusion defect if it gets into the film, so it is effective to use a high-precision filter that can capture more than 95% of foreign matter of 3 μm or more. The film is then extruded into a sheet from a slit die, laminated in the above-mentioned feed block to 100 to 1000 layers, the resin is extruded from a die, and cooled by a casting roll to produce an unstretched film. In this case, it is preferable to install a static mixer and a gear pump in the polymer flow path from the viewpoint of stabilizing the back pressure and suppressing the variation in layer thickness.
[0033] The stretching method may be sequential biaxial stretching or simultaneous biaxial stretching. Simultaneous biaxial stretching is preferred because it does not involve stretching with rolls, and therefore can suppress localized heating unevenness on the film surface, obtain uniform quality, and suppress the occurrence of scratches due to speed differences at the contact points between the film and rolls and transfer of minute scratches from the rolls that accompany roll stretching during stretching, while sequential biaxial stretching is preferred because it can individually and precisely control the properties in the longitudinal and transverse directions.
[0034] In the simultaneous biaxial stretching, an unstretched film is first stretched simultaneously in the longitudinal direction and the transverse direction at a stretching temperature of 80°C to 125°C, preferably 85°C to 120°C. If the stretching temperature is lower than 80°C, the film is likely to break, and if the stretching temperature is higher than 125°C, sufficient strength may not be obtained. In addition, from the viewpoint of preventing stretching unevenness, the total stretching ratio in the longitudinal direction and the transverse direction is 4 times to 20 times, preferably 6 times to 15 times. If the total stretching ratio is less than 4 times, it is difficult to obtain sufficient strength. On the other hand, if the ratio is more than 20 times, the film is likely to break, and stable production of the film may be difficult. In order to obtain the necessary strength, it is preferable to perform another stretching at a temperature of 140°C to 200°C, preferably 160°C to 190°C, in the longitudinal direction and / or width direction at 1.02 times to 1.5 times, preferably 1.05 times to 1.2 times, so that the total stretching ratio is 3.0 times to 4.5 times, preferably 3.2 times to 4.0 times, and 3.2 times to 5.0 times, preferably 3.5 times to 4.3 times in the longitudinal direction and width direction. Then, heat setting is performed at 205°C to 240°C, preferably 220°C to 240°C, for 0.5 seconds to 20 seconds, preferably 1.0 seconds to 15 seconds. If the heat setting temperature is lower than 205°C, the thermal crystallization of the film does not proceed, so that the target dimensional change rate may be difficult to stabilize. In addition, in order to stabilize the film physical properties, the temperature difference between the top and bottom of the film during heat treatment is 20°C or less, more preferably 10°C or less, and even more preferably 5°C or less. If the temperature difference between the top and bottom of the film is greater than 20°C, it may cause deterioration of flatness during heat treatment. After that, the film is subjected to a relaxation treatment of 0.5% to 7.0% in the longitudinal and / or transverse directions in a slow cooling section.
[0035] On the other hand, the film of the present invention can also be produced by sequential biaxial stretching. The stretching temperature for the first longitudinal stretching is 80°C or higher and 125°C or lower, preferably 85°C or higher and 120°C or lower. If the stretching temperature is lower than 80°C, the film is likely to break, and if the stretching temperature is higher than 125°C, the film surface may be easily damaged by heat. The stretching ratio is 3.0 times or higher and 4.5 times or lower in the longitudinal direction, preferably 3.2 times or higher and 4.0 times or lower. The stretching temperature for the subsequent widthwise stretching is 80°C or higher and 125°C or lower, preferably 85°C or higher and 120°C or lower. The stretching ratio is 3.2 times or higher and 5.0 times or lower in the widthwise direction, preferably 3.5 times or higher and 4.3 times or lower. If the temperature and ratio are outside the above ranges, problems such as uneven stretching or film breakage may occur, and the film characteristic of the present invention may be difficult to obtain. In particular, when the stretching ratio during longitudinal stretching is high, the dimensional change rate in the longitudinal direction at a heating temperature of 140°C is likely to exceed 0.20%. The film thus sequentially biaxially stretched is subjected to a re-longitudinal stretching similar to the above-mentioned simultaneous biaxial stretching, or is directly stretched transversely, passed through an intermediate cooling section, and then heat-set at 205°C to 240°C, preferably 210°C to 230°C, for 0.5 seconds to 20 seconds, preferably 1.0 seconds to 15 seconds. If the heat-setting temperature is lower than 205°C, the crystallization of the film does not proceed, so the structure is not stable, and the target characteristics such as the dimensional change rate may not be obtained. Then, in the slow cooling section, a relaxation treatment of 0.5% to 7.0% in the longitudinal and / or transverse directions is performed.
[0036] In the sequential biaxial stretching, the longitudinal stretching process is a process in which the film and the rolls come into contact with each other, and scratches are likely to occur due to the difference between the peripheral speed of the rolls and the speed of the film, so a driving method in which the peripheral speed of the rolls can be set individually for each roll is preferred. In the longitudinal stretching process, the material of the transport roll is selected depending on whether the unstretched film is heated to the glass transition point or higher before stretching, or whether the unstretched film is transported to the stretching zone while being kept at a temperature below the glass transition point, and is heated all at once during stretching. When the unstretched film is heated to the glass transition point or higher before stretching, it is preferable to select from non-adhesive silicone rolls, ceramics, and "Teflon" (registered trademark) in order to prevent adhesion due to heating. In addition, the stretching rolls are the process in which the film is most heavily loaded and scratches and uneven stretching are likely to occur in the process, so the surface roughness (arithmetic mean roughness) Ra of the stretching rolls is 0.005 μm to 1.0 μm, preferably 0.1 μm to 0.6 μm. If the surface roughness Ra is greater than 1.0 μm, the unevenness of the roll surface may be transferred to the film surface during stretching, and if it is less than 0.005 μm, the roll and the film surface may stick to each other, making the film more susceptible to heat damage. In order to control the surface roughness Ra, it is effective to appropriately adjust the grain size of the abrasive, the number of times of grinding, etc. In the case where the unstretched film is transported to the stretching zone while being kept at a temperature below the glass transition point and is heated all at once during stretching, it is preferable to use a metal roll with a surface roughness Ra of 0.2 μm to 0.6 μm that has been surface-treated with hard chrome or tungsten carbide as the transport roll in the preheating zone. In addition, the film may be relaxed in the longitudinal and / or transverse directions during heat treatment.
[0037] The film of the present invention thus obtained has a low haze value and an excellent color tone b value, and therefore has excellent transparency, and can be used for various purposes such as optical films for protecting polarizing plates and conductive panel substrates, release films, electronic component protection films, etc. In addition, it is advantageous in terms of environmental protection efforts because a large amount of recycled polyester resin can be used. EXAMPLES
[0038] The present invention will be described in more detail below based on comparative examples and examples, although the present invention is not limited to the following examples.
[0039] [Evaluation method of physical properties] (1) Haze value (%) Five 10cm x 10cm square pieces were cut out from the polyester film and used as sample pieces. The surface haze of these sample pieces was measured using a haze meter HZ-V3 (manufactured by Suga Test Instruments Manufacturing Co., Ltd.) (old JIS-K-7105 (1981)). This was measured once from one side and once from the other side for each sample piece, and the data for all 10 samples of five sample pieces was averaged to obtain the haze value (%). When the width direction was known, five 10cm x 10cm square pieces were cut out at the center in the width direction, and when the width direction was unknown, such as in the case of a cut sample, five 10cm x 10cm square pieces were cut out at an arbitrary position.
[0040] (2) Film color tone b value Using the sample pieces cut out in (1), the color tone of the film was measured by the transmission method (JIS-Z8722 (2009)) using a spectrophotometer ZE-2000 manufactured by NIPPON DENSHOKU Co., Ltd. This was measured five times from one side and five from the other side, and the total data of 10 was averaged to obtain the color tone b value.
[0041] (3) Film thickness T (μm), average thickness of each layer (μm), number of layers The sample pieces cut out in (1) were measured according to the micrometer method (JIS-C-2151 (2019)). When the thickness was 50 μm or less, 10 sheets were stacked and measured, and the result was divided by the number of sheets to obtain the thickness per sheet.
[0042] The average thickness of each layer was measured by cutting out cross sections of five sample pieces cut out in (1) using a microtome, observing the cross sections of the film at 10,000 to 40,000 times magnification using a transmission electron microscope H-7100FA type (manufactured by Hitachi, Ltd.) at an acceleration voltage of 75 kV, taking cross-sectional photographs, and measuring the number of layers and the thickness of each layer. The thickness of each layer was measured from any five points per sample piece in the thickness direction of the sample piece, and the average value was taken as the average thickness of each layer. When the layers were difficult to confirm, a staining technique using known RuO4, OsO4, etc. was used to increase the contrast.
[0043] When the number of layers and the thickness of each layer could not be determined from the film, the thickness of each layer was determined from the discharge ratio (lamination ratio) by the gear pump in the manufacturing process and the number of layers and film thickness T described below, and this was taken as the average thickness. The number of paths corresponding to the layers constituting the film was then counted to obtain the number of layers.
[0044] (4) Recycled polyester resin content of each layer and recycled polyester resin content of the film (mass%) When producing the film, the mass of each polyester resin raw material fed into each extruder was measured. For each layer or film, the constituent polyester resin raw material was taken as 100% by mass, and the proportion of recycled polyester resin raw material was taken as the content of each recycled polyester resin. If each polyester resin raw material contains an additive, the additive content was subtracted from the polyester resin raw material to calculate.
[0045] (5) Color tone b value of each polyester resin Pellets of the polyester resin raw material were filled into a cylindrical powder measurement cell and measured by the reflection method using a color difference meter (SM Color Meter SM-T, manufactured by Suga Test Instruments Co., Ltd.), and this was taken as the color tone b value of each polyester resin.
[0046] (6) Color tone b value of the polyester resin that constitutes the film The polyester resin constituting the polyester film is taken as 100% by mass, and each polyester resin raw material is converted to a 100% ratio constituting the polyester film, and the ratio of each polyester resin raw material is multiplied by the color tone b value of that polyester raw material obtained in (5). The sum of the multiplied values is divided by 100 to obtain the color tone b value of the polyester resin constituting the film.
[0047] (7) Change in color tone b value The color tone b value (A) of the polyester resin constituting the film calculated in (6) above was divided by the color tone b value (B) of the film measured in (2) and the result was rounded off to two decimal places.
[0048] [Preparation and properties of polyethylene terephthalate resin] (PET-1) Terephthalic acid was used as the acid component, ethylene glycol as the glycol component, and antimony trioxide (polymerization catalyst) was added to the polyester pellets to give 300 ppm of antimony atom, and a polycondensation reaction was carried out to obtain polyethylene terephthalate resin. The intrinsic viscosity of the obtained polyethylene terephthalate resin was 0.65 dl / g, and the color tone b value was 4.5. This is called PET-1.
[0049] (PET-2) The polyethylene terephthalate film of the following [Reference Example 1 (Production method of polyester film)] was pulverized, and the pulverized recovered polyester was melted in an extruder, extruded from a die in the form of a strand, and rapidly solidified with cold water. The solidified strand was cut into pellets with a strand cutter to obtain a polyethylene terephthalate resin. The intrinsic viscosity of the obtained polyethylene terephthalate resin was 0.62 dl / g, and the color tone b value was 10.0. This was designated PET-2.
[0050] (PET-3) The polyethylene terephthalate film of the following [Reference Example 1 (Production method of polyester film)] was pulverized, and then immersed in a mixed aqueous solution (pH 13.5) containing 1% by mass of a nonionic surfactant of a polyoxyethylene derivative and 3% by mass of sodium hydroxide, and treated at 105°C for 30 minutes, and then washed with water and dried. The sodium hydroxide-treated polyester was melted in an extruder, extruded from a die in the form of a strand, and rapidly solidified with cold water. The solidified strand was cut into pellets with a strand cutter to obtain a polyethylene terephthalate resin. The intrinsic viscosity of the obtained polyethylene terephthalate resin was 0.61 dl / g, and the color tone b value was 13.5. This was designated PET-3.
[0051] (PET-4) The polyethylene terephthalate film of the following [Reference Example 1 (Production method of polyester film)] was pulverized, and then immersed in a mixed aqueous solution (pH 13.5) containing 1% by mass of a nonionic surfactant of a polyoxyethylene derivative and 3% by mass of sodium hydroxide, and treated at 120°C for 60 minutes, and then washed with water and dried. The sodium hydroxide-treated polyester was melted in an extruder, extruded from a die in the form of a strand, and rapidly solidified with cold water. The solidified strand was cut into pellets with a strand cutter to obtain a polyethylene terephthalate resin. The intrinsic viscosity of the obtained polyethylene terephthalate resin was 0.59 dl / g, and the color tone b value was 20.0. This was designated PET-4.
[0052] [Reference Example 1 (Method of manufacturing polyester film)] Polyethylene terephthalate chips prepared from PET-1, which is substantially free of inert particles, were dried at 180°C for 5 hours under a reduced pressure of 3 torr, fed into a melt extruder and melted at 290°C, filtered through five leaf disk filters with a filtering accuracy of 8 μm, and then extruded into a sheet from a T-shaped nozzle. The extruded sheet was cooled and solidified on a mirror-finished casting drum with a surface temperature of 20°C by an electrostatic casting method, to obtain a substantially amorphous unstretched film.
[0053] This unstretched film was first preheated to 75°C using a group of continuously arranged rolls, then heated using rolls at 90°C and stretched longitudinally (in the running direction of the film) at a stretch ratio of 3.3 times. It was then cooled using a group of cooling rolls to produce a uniaxially oriented (uniaxially stretched) film.
[0054] The film was then introduced into a stenter oven and stretched 4.0 times in the transverse direction (perpendicular to the running direction of the film) at 100°C, followed by heat treatment at 230°C and 5% relaxation in the transverse direction in the same oven, and then cooled to 100°C to obtain a biaxially stretched polyester film with a thickness of 50 μm. The physical properties are shown in the table.
[0055] [Comparative Examples 1 to 3] Polyester films were obtained in the same manner as in Reference Example 1, except that the thickness of the unstretched film and the stretch ratio of the film were adjusted to the thicknesses shown in the table, and that the polyester resins shown in the table were used for the resin configuration of the layers. The physical properties of these films are shown in the table.
[0056] [Comparative Example 4] Except for using the polyester resins shown in the table, polyester films were obtained in the same manner as in Reference Example 1. The physical properties of these films are shown in the table.
[0057] [Example 1] The polyethylene terephthalate chips prepared from PET-1 and PET-2, which are substantially free of particles, were dried at a temperature of 180 ° C. for 5 hours under a reduced pressure of 3 torr, and the polyester resin constituting layer A was 70% by mass of PET-1 and 30% by mass of PET-2, and the polyester resin constituting layer B was 70% by mass of PET-1 and 30% by mass of PET-2. Each was melted at 290 ° C. in a separate extruder, and after passing through five leaf disk filters with a filtration accuracy of 8 μm, resin A and resin B were laminated by the method described in JP 2007-307893 A while measuring so that the lamination width was the same, and the layers were alternately merged so that layer A was placed on the surface layer of the film in a lamination device with a 603-layer feed block (layer A was 302 layers, layer B was 301 layers). The laminated molten resin was then fed to a T-die and molded into a sheet, after which it was rapidly cooled and solidified on a casting drum maintained at a surface temperature of 25°C while applying an electrostatic voltage of 8 kV with a wire, to obtain a substantially amorphous unstretched film. A biaxially stretched polyester film was obtained in the same manner as in the polyester film manufacturing method except for the above. The physical properties of this film are shown in the table.
[0058] [Examples 2 to 5] A biaxially stretched polyethylene terephthalate film was obtained in the same manner as in Example 1, except that the polyester resins used in Layer A and Layer B were polyester resins as shown in the table. The physical properties of this polyethylene terephthalate film are shown in the table.
[0059] [Examples 6 and 7] A biaxially stretched polyester film was obtained in the same manner as in Example 2, except that the feed block in Example 1 was replaced with a lamination device having the number of layers shown in the table. The physical properties of this film are shown in the table.
[0060] [Examples 8 and 9] A biaxially stretched polyester film was obtained in the same manner as in Example 2, except that the film formation speed was changed to obtain the film thickness shown in the table. The physical properties of this film are shown in the table.
[0061] [Example 10] A biaxially stretched polyester film was obtained in the same manner as in Example 2, except that the film formation speed was changed to obtain the film thickness shown in the table and the resin composition of the layers was shown in the table. The physical properties of this film are shown in the table.
[0062] [Table 1]
[0063] [Table 2]
Claims
1. A film formed by laminating 100 to 1,000 polyester resin layers, the film containing 30% by mass to 100% by mass of recycled polyester resin relative to the total mass of the polyester resin constituting the film.
2. 2. The film according to claim 1, wherein the average thickness of the polyester resin layer is from 10 nm to 1,000 nm.
3. 2. The film according to claim 1, wherein the color tone b value of the film is from -2.0 to 2.
0.
4. 2. The film according to claim 1, wherein the color tone b value of the polyester resin constituting the film is more than 4.0 times the color tone b value of the film.
5. 2. The film according to claim 1, wherein the color tone b value of the polyester resin is 5.0 or more and 15.0 or less.
6. 2. The film according to claim 1, wherein the color tone b value of the recycled polyester resin is 5.0 or more and 30.0 or less.
7. 2. The film of claim 1, wherein the film has a haze value of 2.0% or less.
8. The film according to claim 1 , wherein the thickness T (μm) of the film is 25 μm or more and 500 μm or less.
9. A method for producing a film comprising 100 to 1,000 polyester resin layers according to any one of claims 1 to 8, wherein the film contains 30% by mass or more and 100% by mass or less of recycled polyester resin relative to the total mass of the polyester resin constituting the film.
Citation Information
Patent Citations
Regenerated film
JP1996217892A
Laminated polyester film
JP2012210761A